2022
DOI: 10.1155/2022/5040458
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Development of an Age-Related Classification and Signature to Predict Prognosis and Immune Landscape in Osteosarcoma

Abstract: Background. In childhood and adolescence, the prevailing bone tumor is osteosarcoma associated with frequent recurrence and lung metastasis. This research focused on predicting the survival and immune landscape of osteosarcoma by developing a prognostic signature and establishing aging-related genes (ARGs) subtypes. Methods. The training group comprised of the transcriptomic and associated clinical data of 84 patients with osteosarcoma accessed at the TARGET database and the validation group consisted of 53 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Cellular senescence has been studied in various cancer types and compelling evidences have revealed that cellular senescence is associated with cancer prognosis (Dai et al, 2022a;Domen et al, 2022a;Domen et al, 2022b). Development of senescence-related classification and characterization of senescence-based signature have attracted much attention in tumor research (Feng et al, 2022a;Hong et al, 2022). However, the mechanisms of cellular senescence in COAD, as well as the specific prognostic signatures are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence has been studied in various cancer types and compelling evidences have revealed that cellular senescence is associated with cancer prognosis (Dai et al, 2022a;Domen et al, 2022a;Domen et al, 2022b). Development of senescence-related classification and characterization of senescence-based signature have attracted much attention in tumor research (Feng et al, 2022a;Hong et al, 2022). However, the mechanisms of cellular senescence in COAD, as well as the specific prognostic signatures are poorly understood.…”
Section: Introductionmentioning
confidence: 99%